Noise landing charges and passengers' choice of airport. - Yeahiya, Mohammed (Cranfield University, 1995)
This study demonstrates how aircraft noise can be translated into a form of landing charge. The objectives of the thesis were to develop noise landi'ng charges for six of the major airports in England and to determine what the implication it has on passengers' choice of airports. An airport choice model is developed distinguished by three market types: long-haul international scheduled, short-haul international scheduled and charter international. Modelling of airport choice was also carried out for passengers from the Greater London and South East areas. The best results are obtained using difference in access time, logarithmic difference in frequencies and weighted differences in fare variables. There is consistency in the access time coefficients for all three markets. Airport choice for international scheduled and charter passengers for the Greater London and other South East areas also show consistency in access time amongst different passenger groups in choosing airports. The implication of the noise charge particularly at Gatwick and Heathrow for the short and long haul markets reveal that the fare coefficients are sensitive and are subject to doubt. However Brooke et al (1994) acknowledge that exact fare details are difficult to obtain. Therefore it is a difficult task to produce accurate fare coefficients with published fare details that do not take into account discounts received by passengers. This is reflected in this study by observing the fact that high number of passengers change airports, when it may be argued that the noise charges are moderate. The sensitivity of the implications of the noise charge determined in this study have depended highly on the fare coefficients. This study has demonstrated the importance and perhaps the over reliance of depending on a single parameter for the evaluation of the implications of the noise charge.